Sektor Informal, Pengangguran dan Kemiskinan di Provinsi Bali Tahun 2004 - 2010 - Mahaprajna Paramita, Desak Ayu; Suresmiathi D, Anak Agung Ayu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2012)
The informal sector is a small-scale economic activities are considered as a form of employment situation of the growth opportunities in the province of Bali. Unemployment and poverty are problems in economic development, there is no right way to solve this problem. Issues to be discussed is how to simultaneously and partially influence of the informal sector and unemployment on poverty in the province of Bali in 2004 to 2010. The results of this study indicate that simultaneous informal sector and significant effect on the reduction of unemployment in the province of Bali in 2004 to 2010. From the test results partially informal sector and significant negative effect on poverty in the province of Bali in 2004 to 2010. While unemployment is not a positive and significant effect partially on poverty in the province of Bali in 2004 to 2010.
Keywords: Informal Sector; Unemployment; Poverty